Almost no memory - Davis, Lydia 1947- (Farrar, Straus & Giroux, 1997)
Stories by an experimental writer, ranging in length from a sentence to several pages. One story describes the way a few ill-chosen words can turn a minor dispute into high drama, another is on the bad luck of an explorer who accomplishes a perilous expedition, only to die on his way home. By the author of The End of the Story.
Keywords: Short stories